WAJIB DAFTAR JAMINAN FIDUSIA DALAM PEMBIAYAAN MUDHARABAH Efektivitas Pelaksanaan Pasal 11 Undang-Undang RI Nomor 42 Tahun 1999 Tentang Jaminan Fidusia di BMT Kota Pekalongan - Sofiani, Triana (Jurnal Penelitian, 2015)
This study aims to analyze the effectiveness of the implementation of compulsory registration of fiduciary insurance as the provisions of Article 11 of Law No. 42 of 1999 concerning fiduciary in Mudharabah in Baitul Maal Wat Tamwil (BMT) Pekalongan and legal implication in terms of fiduciary insurance is not registered at the Office Registration Fiducia. Interviews and literary studies are used to collect data and data triangulation is used to check its credibility while Interactive Model is used to analyze data. The results showed that, as the fiduciary guarantee registration requirement contained in Article 11 (1) Fiduciary Insurance Law is not effective to be implemented, because: 1) substantially the article is not yet understood by all communities affected by the regulations; 2) law enforcement officials have not provided services to the fullest; 3) the legal infrastructure (legal facilities) are available yet provide ease and convenience to be able to access in implementing such regulations and; 4) lack of legal awareness of the managers of BMT. Legal consequences will occur if the fiduciary is not registered to the fiduciary registration office, namely: 1) non-fulfillment of the principle of specialties and publicity; 2) no preferent rights (the right to precedence) in the payment of the debt, if the debtor break a promise; 3) does not have the executorial power.